Frailty predicts mortality in all emergency surgical admissions regardless of age. An observational study. (19th February 2019) - Hewitt, J; Carter, B; McCarthy, K; Pearce, L; Law, J; Wilson, F V; Tay, H S; McCormack, C; Stechman, M J; Moug, S J; Myint, P K
Abstract: Background: frail patients in any age group are more likely to die than those that are not frail. We aimed to evaluate the impact of frailty on clinical mortality, readmission rate and length of stay for emergency surgical patients of all ages. Methods: a multi-centre prospective cohort study was conducted on adult admissions to acute surgical units. Every patient presenting as a surgical emergency to secondary care, regardless of whether they ultimately underwent a surgical procedure was included. The study was carried out during 2015 and 2016. Frailty was defined using the 7-point Clinical Frailty Scale. The primary outcome was mortality at Day 90. Secondary outcomes included: mortality at Day 30, length of stay and readmission within a Day 30 period. Results: the cohort included 2, 279 patients (median age 54 years [IQR 36–72]; 56% female). Frailty was documented in patients of all ages: 1% in the under 40's to 45% of those aged 80+. We found that each incremental step of worsening frailty was associated with an 80% increase in mortality at Day 90 (OR 1.80, 95% CI: 1.61–2.01) supporting a linear dose–response relationship. In addition, the most frail patients were increasingly likely to stay in hospital longer, be readmitted within 30 days, and die within 30 days. Conclusions: worsening frailty at any age is associated with significantly poorer patient outcomes, including mortality in unselected acute surgical admissions. Assessment of frailty should be integrated into emergency surgical practice to allow prognostication and implementation of strategies to improve outcomes.